PERAN BAHAN ORGANIK DAN TATA AIR MIKRO TERHADAP KELARUTAN BESI, EMISI CH4, EMISI CO2 DAN PRODUKTIVITAS PADI DI LAHAN SULFAT MASAM - , WAHIDA ANNISA YUSUF ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Soil acidity, high Al and Fe contents are the problems encountered in swampland. The study aimed to: (1) find out and identify the characteristics of natural acid sulphate soil and intensively developed acid sulphate soil, as well as the characteristics of local organic matter used a neutralizer of acidity, (2) find out the kind of organic matter and the system of water structure in improving the nature of acid sulphate soil and increasing the growth of rice, (3) examine the effect of local organic matter and NPK fertilizing on increasing the productivity of rice and reducing the emission of CH4 and CO2 in acid sulphate land The study was a series of experiments as follows: The first stage dealt with the characterization of acid sulphate soil and organic matter